Prediction of far-field noise from installed corrugated nozzles - de Souza, Francisco J.; Lawrence, Jack; Cruz, Ricardo H.; Proenca, Anderson R. (American Institute of Aeronautics and Astronautics (AIAA), 2024)
In this study, a reduced order model, devised by Lyu and Dowling, is used to predict the farfield installation noise of corrugated nozzles installed beneath a NACA aerofoil. A complementary investigation, detailed in another paper, reveals that employing square corrugations near the nozzle lip diminishes jet-surface interaction (JSI) noise compared to a round 40-mm diameter nozzle. This reduction is particularly notable for Strouhal numbers ranging from 0.3 to 0.9 and at high polar angles. The near-field pressure data, required for Lyu and Dowling’s model, is gathered using a circular array consisting of eight 1/8-inch microphones in the Doak Laboratory, at the University of Southampton, UK. Generally, the predictions align well with the experimental trends for Mach numbers ranging from 0.4 to 1 under static ambient flow conditions. Furthermore, it is observed that a minimum of four azimuthal modes must be available to accurately predict the noise generated by the corrugated nozzles. The effects of free-stream Mach number, particularly focusing on the predictive capacity of Lyu and Dowling’s model, are also investigated. Quantitative agreement at Strouhal numbers between 0.1 and 0.5 in evidenced.